Cardiac Involvement by HIV-Associated DLBCL - Charles T. Mupamombe; Jude Noel; Derek B. Laskar; Liza Valdivia (Case Reports in Medicine)
Non-Hodgkin’s lymphoma (NHL) is a common AIDS-defining malignancy among people living with HIV. Of the different types of NHLs, diffuse large B-cell lymphoma (DLBCL) is the most common. Prognosis of DLBCL has improved over the years in the general population but remains relatively poor in HIV-positive individuals. Almost any organ system can be affected by DLBCL; however, cardiac involvement remains rare and suggests aggressive disease. We present a case of DLBCL in an HIV-positive patient, who had cardiac involvement, with the only clue to cardiac involvement being symptom being tachycardia and dysphagia.